2011
DOI: 10.33073/pjm-2011-033
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Step Strategy for Molecular Typing of Multidrug-Resistant Mycobacterium tuberculosis Clinical Isolates from Poland

Abstract: Tuberculosis (TB) continues to be one of the most challenging public health problems in the world. An important contributor to the global burden of the disease is the emergence and spread of drug-resistant and particularly multidrug-resistant Mycobacterium tuberculosis strains (MDR), defined as being resistant to at least isoniazid and rifampicin. In recent years, the introduction of different DNA-based molecular typing methods has substantially improved the knowledge of the epidemiology of TB. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In addition, other studies revealed that the calculated discriminatory power of IS6110‐Mtb1/Mtb2 PCR was greater than those of MIRU‐VNTR typing and spoligotyping and almost equivalent to that of IS6110‐RFLP genotyping (Jagielski et al . 2011, 2016). However, in a study in Poland, the differentiating power of clustering via IS6110‐Mtb1‐Mtb2 PCR was only slightly minor than RFLP‐IS6110 (Sajduda et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other studies revealed that the calculated discriminatory power of IS6110‐Mtb1/Mtb2 PCR was greater than those of MIRU‐VNTR typing and spoligotyping and almost equivalent to that of IS6110‐RFLP genotyping (Jagielski et al . 2011, 2016). However, in a study in Poland, the differentiating power of clustering via IS6110‐Mtb1‐Mtb2 PCR was only slightly minor than RFLP‐IS6110 (Sajduda et al .…”
Section: Discussionmentioning
confidence: 99%
“…The patterns obtained from IS6110‐Mtb1/Mtb2 PCR typing using each of the combinations of primers (Mtb1‐IS1‐IS2 or Mtb2‐IS1‐IS2), were analysed separately with Lab Works 4.5 software (UVP Inc., Upland, CA) and by visual inspection as described by Jagielski et al . (2011).…”
Section: Methodsmentioning
confidence: 99%
“…Although the IS 6110 -Mtb1-Mtb2 PCR method has not been exploited sufficiently, the results from the insofar performed studies suggest its usefulness in the molecular epidemiological investigations of TB. Most notably the discriminatory power of this method has been demonstrated as almost equivalent to that of IS 6110 -RFLP typing [ 67 , 148 , 149 ].…”
Section: Methods Based On Gc-rich Sequencesmentioning
confidence: 99%
“…Os métodos de tipagem molecular vêm desempenhando, atualmente, um importante papel na capacidade de discriminar isolados microbianos e, ao mesmo tempo, estabelecer uma relação clonal entre linhagens relacionadas. Constituem, assim, métodos úteis para estudos epidemiológicos que visam prevenir e bloquear cadeias de transmissão de diversas doenças infecciosas (10,22). A aplicação desses métodos tem contribuído significativamente para uma maior compreensão dos casos e da transmissão da tuberculose em diversas regiões do mundo.…”
Section: Introductionunclassified